Bilateral periventricular nodular heterotopia in France: frequency of mutations in FLNA, phenotypic heterogeneity and spectrum of mutations. Issue 12 (16th November 2009) - Solé, G; Coupry, I; Rooryck, C; Guérineau, E; Martins, F; Devés, S; Hubert, C; Souakri, N; Boute, O; Marchal, C; Faivre, L; Landré, E; et al.
Abstract : Bilateral periventricular nodular heterotopia (BPNH) is the most common form of periventricular heterotopia. Mutations in FLNA, encoding filamin A, are responsible for the X linked dominant form of BPNH ( FLNA -BPNH). Recently, atypical phenotypes including BPNH with Ehlers–Danlos syndrome (BPNH-EDS) have been recognised. A total of 44 FLNA mutations have so far been reported in this phenotype. Most of these mutations lead to a truncated protein, but few missense mutations have also been described. Here, the results of a mutation screening conducted in a series of 32 BPNH patients with the identification of 12 novel point mutations in 15 patients are reported. Nine mutations were truncating, while three were missense. Three additional patients with BPNH-EDS and a mutation in FLNA are described. No phenotype–genotype correlations could be established, but these clinical data sustain the importance of cardiovascular monitoring in FLNA -BPNH patients.